PERBEDAAN PENGGUNAAN JAMUR TIRAM PUTIH TERHADAP KADAR PROTEIN DAN SERAT NUGGET AYAM - Desy Andriana Rizky; Agustina Widyasworo; Eddy Trijana Sudani (AVES: Jurnal Ilmu Peternakan, 2018)
This research material is white oyster mushroom chicken nugget. This research method is an experiment by using Completely Randomized Design (RAL). The treatmeant in this research is with the use of white oyster mushroom with 5 treatment that is 0%, 15%, 30%, 45% and 60% where each treatment is repeated 5 times. The result of this study showed the use of white oyster mushrooms can lower protein levels and increase fiber levels and show a very real difference. Treatment P0 without the use of white oyster mushroom showed the value of protein content that is 16,902%. Protein content with the highest value with the use of white oyster mushrooms obtained in treatment P1 with the use of white oyster mushrooms as much 15% with the value of protein content as muc 15,972% and the lowest protein content obtained in treatment P3 with the use of white oyster mushrooms much as 45% 12,718%. The highest level of fiber obtained from the treatment of P2 and P3 with the vlue of fiber content of 0,702% with the use of white oyster mushrooms much as 30% and 45%, while the lowest fiber content obtained at treatment P1 with the use of white oyster mushrooms much as 15% 0,302%. P0 showed a fiber content of 0,222. The protein content obtained from this research is still in standart setting of Indonesian National Standart Body (SNI) that is more protein level at the limit of at least 12% chicken nuggets, while for fiber content obtained from the research is still not sufficient Nutrion Needs Numbers is 25g/day.